Eichhornia crassipes mediated bioinspired synthesis of crystalline nano silver as an integrated medicinal material: a waste to value approach - Moudgil, Aliesha; Deval, Animesh S.; Dharne, Mahesh S.; Sarkar, Dhiman M.; Choudhari, Amit S.; Chaudhari, Bhushan P. (Journal of Cluster Science, 2021)
The present study deals with the synthesis of silver nanoparticles from Eichhornia crassipes. Dynamic light scattering (DLS), Transmission electron microscopy (TEM), UV-Vis spectroscopy, Fourier Transform Infrared (FTIR) spectroscopy and X-ray diffraction (XRD) were performed for nanoparticle characterization. The aqueous plant extract of Eichhornia crassipes was phytochemically analyzed for phenol, flavonoid, reducing sugar content, alkaloids, saponins and carotenoids. The synthesized particles after optimization of important parameters have an average diameter of 12.48 +/- 3.43 nm with a spherical morphology and zeta potential of - 31.53 mV. At 100 mu g/ml of nanoparticle concentration, the antioxidant activity of 93.6% was observed. MIC (Minimum inhibitory concentration) values exhibiting the antimicrobial attributes reported an estimated value of 7.8 mu g/ml for gram-negative and higher values of 31.25 and 250 mu g/ml for gram-positive bacteria. The antibiofilm assay showed 86.89% and 74.7% of the reduction in violacein synthesis and biofilm inhibition respectively at 15 mu g/ml nanoparticle concentration. The anticancer assay reported the IC50 (Inhibitory concentration) values of 13.32, 14.71 and 19.91 mu g/ml for HeLa, HCT 116 and L6 cell lines respectively. Thus the study establishes a significant integrative treatment to combat secondary infections in cancer patients. Graphic
Keywords: antibacterial activity; Antibiofilm activity; Anticancer activity; Antioxidant activity; Eichhornia crassipes; silver nanoparticles

One-pot concurrent biosynthesis of biphasic CuxO (cuprous and cupric oxide) nanoparticles using leaf extract of Eichhornia crassipes and investigation of their potent healthcare applications - Moudgil, Aliesha; Varma, Sanjana; Shinde, Manish D.; Vamkudoth, Koteswara Rao; Sarkar, Dhiman M.; Shende, Rajnigandha A.; Amalnerkar, Dinesh; Chaudhari, Bhushan P. (Emergent Materials, 2022)
Eichhornia crassipes, an aquatic weed, has been used for the one-pot quick synthesis of cuprous and cupric oxide nanoparticles in this report. The identification and validation of the formed nanoparticles were successfully done by sophisticated characterization techniques such as UV–visible spectroscopy, transmission electron microscopy (TEM), X-ray diffraction (XRD), and Fourier transform infrared (FTIR) spectroscopy. Their biomedical interventions were assessed by their antioxidant and anticancer activities. The synthesized nanoparticles have a spherical morphology with an average diameter of 10 nm. Antioxidant assay performed showed an increasing trend in a dose-dependent manner with the percentage radical scavenging activity up to 94.70% at a much higher concentration of 1000 µg/ml. The antioxidant potential at such higher concentration is suspected to invoke a change in the cytotoxic potential of the nanoparticles which is then verified by the MTT assay. A significant cytotoxic activity against HeLa (cervical cancer) and HCT 116 (colorectal carcinoma) cell lines was detected with noted IC50 values of 17.17 and 13.70 µg/ml respectively. The conclusive findings obtained are enough to substantiate the use of these nanoparticles in biomedical areas specifically in anticancer treatment due to their high toxicities. The hazards imposed by Eichhornia crassipes can be alleviated by using them as biofactories for the synthesis of a variety of nanomaterials. This helps in curbing the water pollution issues as well as the developing synthesis protocols for robust and stable nanoparticles.